Effect of Sr, Mg and Fe substitution on the physico-chemical and biological properties of SiCaP multilayer scaffolds - Nayarit A. Mata; Marcela Arango-Ospina; Pablo Velasquez; Angel Murciano; Piedad N. De Aza; Aldo R. Boccaccini (Boletín de la Sociedad Española de Cerámica y Vidrio, 2023)
In this work, a new combination of ceramic materials is proposed for bone tissue engineering applications. Multilayer scaffolds consisting of a core composed mainly of calcium pyrophosphate and external coatings of silica and calcium doped with Fe3+, Sr2+ and Mg2+ were prepared. To study the influence of the arrangement of dopant ions in the external coatings, two different scaffolds were developed: scaffolds 3J consisting of a single external coating with 9 mol% of Fe3+, Sr2+ and Mg2+ ions; and scaffolds 3S comprising three external coatings, each containing 3 mol% of Fe3+, Sr2+ and Mg2+ ions. Scaffolds were physico-chemically characterized and evaluated for in vitro bioactivity and cellular response in the presence of MG-63 cells. The results showed that the core scaffold displayed no in vitro bioactivity or good cellular response, but served as a support for the external coatings given its mechanical resistance. The cell viability of scaffolds 3J and 3S increased more than 100% in relation to the core, and also improved cell proliferation and adhesion resulting in a dense layer of cells that covered the scaffolds’ entire surface. The arrangement of ions in the external coatings did not influence the cellular response, but determined the bioactivity rate. Resumen: En este trabajo se propone una nueva combinación de materiales cerámicos para aplicaciones en ingeniería de tejido óseo. Se prepararon andamios multicapa formados por un núcleo principalmente de pirofosfato cálcico y recubrimientos externos de sílice y calcio dopados con Fe3+, Sr2+ y Mg2+. Para estudiar la influencia de la disposición de los iones dopantes en los recubrimientos externos, se desarrollaron dos andamios diferentes: andamios 3J con un recubrimiento externo con 9 mol% de Fe3+, Sr2+ y Mg2+; y andamios 3S con tres recubrimientos externos, cada uno con 3 mol% de Fe3+, Sr2+ y Mg2+. Posteriormente, se realizó caracterización fisicoquímica, se evaluó su bioactividad in vitro y respuesta celular en presencia de células MG-63. Los resultados mostraron que el núcleo del andamio no presentaba bioactividad ni buena respuesta celular, pero servía de soporte para los recubrimientos externos debido a la resistencia mecánica. La viabilidad celular de los andamios 3J y 3S aumentó en más de 100% respecto al núcleo y mejoró la proliferación y adhesión celular, dando lugar a una densa capa de células en la superficie de los andamios. La disposición de los iones en los recubrimientos externos no influyó en la respuesta celular, pero determinó la tasa de bioactividad.